Analisis Hukum Pidana dalam Penanganan Tindak Pidana Malapraktik Kedokteran (Studi Kasus Putusan Mahkamah Agung Nomor: 871 K/Pid/2018) - Dwi Arys Purwoko (Inovasi Pratama Internasional. Ltd, 2023)
Data from the Indonesian Medical Discipline Honorary Council (MKDKI) shows that cases of malpractice by obstetricians are quite high. For example, a malpractice case that reached the Supreme Court was a team of doctors consisting of dr. Come on, Dr. Hendi Siagian, and dr. Henry Simanjuntak at Dr.Kandau Manado Hospital against the victim, Julia Fransiska Makatey. Another case, malpractice by dr.Heryani Parewasi, Sp.OG. at Anutapura Hospital in Palu against the victim, Nur Indah Restuwati. The two cases of malpractice resulted in a decision by the Supreme Court Judge No. 871K/Pid/2018. The research method in writing this thesis uses normative legal research supported by empirical legal research. Normative legal research is library research to collect data from reference reading materials and laws and regulations, while empirical research is field research, namely the Supreme Court decision No. 871K/Pid/2018. Field research is needed to collect data directly on the objects and subjects referred to in this research. Forms of criminal acts committed by doctors in carrying out their profession are divided into three categories, namely (1) deliberate criminal malpractice; (2) Criminal malpractice that is reckless; and Criminal Malpractice that is negligent. The basis for consideration of the Supreme Court Judges in deciding case No. 871K/Pid/2018, the basic consideration is that the Defendant did not convey to the victim's family about the possibilities that could happen to the victim and sentenced him to 10 months in prison. Mechanism for resolving medical malpractice cases A civil or criminal lawsuit, in this case a dispute between doctors and hospitals dealing with patients and their families or their proxies, can be resolved in two ways, namely litigation (through the judicial process) and non-litigation (outside the judicial process). Justice). It is better if Law Number 29 of 2004 concerning Medical Practice is formulated regarding medical malpractice along with explanations so that the general public, doctors and the world of health can understand and know the criteria for criminal acts of medical malpractice.